Kopi Arabika Sebagai Ide Penciptaan Karya Seni Grafis - Septian Pebin Putra; Rajudin Rajudin; Elvis Elvis (V-art: Journal of Fine Art, 2023)
ABSTRACTThis article discusses the creation of five graphic artworks that use Arabica coffee as a creative subject. The reason for choosing Arabica coffee as the main subject is because it is extensively cultivated in the Kerinci region. Additionally, Arabica coffee fruits have diverse and attractive shapes and colors, such as light green, dark green, yellow, and red. Arabica coffee is transformed into graphic artworks by combining the techniques of hardboardcut and stencil. A representational form is the approach used in the creation of these artworks. The concepts of distortion and disformation are applied in shaping the artworks. The result of this creation is five graphic artworks titled "Ingak," "Proses," "Bakumpao," "Antae," and "Sabae." Each artwork presents a unique interpretation of Arabica coffee, with emphasis on the aspects of shape and color of the coffee fruits. This creation offers a fresh perspective on Arabica coffee through graphic art and depicts the diversity and visual appeal of Arabica coffee fruits. These graphic artworks can provide a deeper appreciation for Arabica coffee as a creative subject and enrich the understanding of graphic art within the cultural context of coffee.Keywords: arabica coffee, representational, distortion, printmakingABSTRAKArtikel ini membahas penciptaan lima karya seni grafis yang menggunakan kopi arabika sebagai objek kreatif. Alasan pemilihan kopi arabika sebagai objek utama adalah karena kopi arabika banyak dibudidayakan di daerah Kerinci. Selain itu, buah kopi arabika memiliki beragam bentuk dan warna yang menarik, seperti hijau muda, hijau tua, kuning, dan merah. Kopi arabika diwujudkan dalam bentuk karya seni grafis dengan menggabungkan teknik hardboardcut dan stencil. Bentuk representasional merupakan pendekatan yang digunakan dalam penciptaan karya ini. Konsep distorsi dan disformasi diterapkan dalam penggarapan bentuk karya. Hasil dari penciptaan ini adalah lima buah karya seni grafis yang diberi judul "Ingak", "Proses", "Bakumpao", "Antae", dan "Sabae". Setiap karya menampilkan interpretasi unik dari objek kopi arabika, dengan penekanan pada aspek bentuk dan warna buah kopi. Penciptaan ini memberikan pandangan baru tentang kopi arabika melalui seni grafis dan menggambarkan keberagaman dan daya tarik visual buah kopi arabika. Karya seni grafis ini dapat memberikan apresiasi yang lebih dalam terhadap kopi arabika sebagai objek kreatif, serta memperkaya pemahaman tentang seni grafis dalam konteks budaya kopi.Kata Kunci: kopi arabika, representasional, distorsi, seni  grafis